SAOL 11 - faksimil - Språkbanken Text (University of Gothenburg, 2025)
Words i SAOL with links to facsimiles.

Ord i SAOL med länkar till faksimiler.
SAOL 11 - faksimil
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik